2019
DOI: 10.1108/ijwbr-01-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Emotions among winery tourists: new vs old wine world

Abstract: Purpose This study aims to compare the influence of emotions produced by the wine and the winery visit on wine purchase intent at two destinations with different cultural views (old and new wine worlds). Design/methodology/approach A quantitative approach was adopted using a total sample of 600 tourists from two different wineries, one in La Rioja (Spain, Europe) and the other in Baja California (Mexico, North America). All the tourists surveyed at the European winery were European, and all the tourists surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 104 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…It has been widely demonstrated that emotions among winery tourists in both the old and new wine worlds are seen as a way to directly establish intensity and engagement in wine tourists visiting wineries and wine regions, depending on whether the wine destinations were located in the new or old wine world (Pelegrín-Borondo et al , 2019). With regard to the dimensions of wine tourism experience emotions, Santos et al (2020) found that wine experience dimensions are influenced by four dimensions: wine storytelling, wine tasting excitement, wine involvement and winescape, which can measure the holistic behaviour of wine tourists (Santos et al , 2020).…”
Section: Literature Background – Key Domains Included In the Framewor...mentioning
confidence: 99%
“…It has been widely demonstrated that emotions among winery tourists in both the old and new wine worlds are seen as a way to directly establish intensity and engagement in wine tourists visiting wineries and wine regions, depending on whether the wine destinations were located in the new or old wine world (Pelegrín-Borondo et al , 2019). With regard to the dimensions of wine tourism experience emotions, Santos et al (2020) found that wine experience dimensions are influenced by four dimensions: wine storytelling, wine tasting excitement, wine involvement and winescape, which can measure the holistic behaviour of wine tourists (Santos et al , 2020).…”
Section: Literature Background – Key Domains Included In the Framewor...mentioning
confidence: 99%
“…Wine tourism is a hedonic experience involving senses and emotions (Brochado et al , 2021; Pelegrín-Borondo et al , 2020). While the multi-dimensionality of wine tourism experiences is a popular research agenda, its multi-sensorial nature is largely under-researched and presents an opportunity for further studies (Brochado et al , 2021).…”
Section: Agenda For Future Researchmentioning
confidence: 99%
“…Four important areas for research emerge based on thematic mapping and examination of literature (Figure 6). 5.1 Multi-sensorial nature of wine tourism experiences Wine tourism is a hedonic experience involving senses and emotions (Brochado et al, 2021;Pelegrín-Borondo et al, 2020). While the multi-dimensionality of wine tourism experiences is a popular research agenda, its multi-sensorial nature is largely under-researched and presents an opportunity for further studies (Brochado et al, 2021).…”
Section: Agenda For Future Researchmentioning
confidence: 99%
“…Other studies indicate that early exposure to flavours (Blake, 2006), the actual food exposure (Zellner et al , 1999) and tasting experiences are the most relevant factors (Giacalone et al , 2014). Moreover, other authors report that product familiarity (Birch, 1999), the individual personality traits (Cardello et al , 2019) or even emotions (Pelegrín-Borondo et al , 2019) influence flavour and food preferences.…”
Section: Literature Reviewmentioning
confidence: 99%